2020
DOI: 10.1136/bmjspcare-2019-002097
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and actual place of death in haematological malignancies: a report from the UK haematological malignancy research network

Abstract: ObjectivesHospital death is comparatively common in people with haematological cancers, but little is known about patient preferences. This study investigated actual and preferred place of death, concurrence between these and characteristics of preferred place discussions.MethodsSet within a population-based haematological malignancy patient cohort, adults (≥18 years) diagnosed 2004–2012 who died 2011–2012 were included (n=963). Data were obtained via routine linkages (date, place and cause of death) and abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…Additionally, perhaps patients find physical and emotional comfort at home [25]. The results are similar to previous studies which also reported that most patients preferred a home death [3,9,12,26].…”
Section: Main Findings and Implications For Clinical Practicesupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, perhaps patients find physical and emotional comfort at home [25]. The results are similar to previous studies which also reported that most patients preferred a home death [3,9,12,26].…”
Section: Main Findings and Implications For Clinical Practicesupporting
confidence: 88%
“…Home-based palliative care enables patients who are terminally ill to be cared for at home and aims to improve their quality of life [2]. Many people prefer to be taken care of at home and also prefer a death at home compared to other settings, such as a hospital or hospice [3,4]. A better understanding of the determinants of preference for place of death may assist to actualize those preferences, while achieving a preferred place of death is considered an indicator of high-quality end-of-life care [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In addition, they should be revisited during the disease course because patients' preferences may evolve. 18 Although early engagement in these discussions is essential, this is difficult to operationalize in real time for patients with aggressive lymphomas. Therefore, practical triggers to conduct these conversations are critical (Table 2).…”
Section: Optimizing Goals-of-care Discussion For Patients With Aggressive Lymphomasmentioning
confidence: 99%
“…Patients who engage in goals-of-care discussions with their hematologic oncologists are more likely to receive care that is consistent with their preferences, to receive specialty palliative care, and to enroll in hospice. [16][17][18] They are also less likely to experience intensive EOL health care use (eg, multiple hospital admissions, hospital death), 19 with corresponding improvement in QOL, reduced risk of complicated grief for bereaved caregivers, and lower health care costs. 16 Patients with aggressive lymphomas have substantial palliative care needs, including fatigue, dyspnea, depression, and pain, which typically worsen near the EOL.…”
Section: Benefits Of Palliative Carementioning
confidence: 99%